Preparation of mupirocin-loaded polymeric nanocapsules using essential oil of rosemary (Brazilian Journal of Pharmaceutical Sciences, 2017)
The purpose of this study was to prepare and characterize mupirocin-loaded polymeric nanocapsules using two different oils and to develop and validate an analytical method for quantitative determination by high performance liquid chromatography. The mean size of the nanoparticles was 233.05 nm and 275.03 nm for nanocapsules with a rosemary oil like oily core and caprylic/capric triglyceride, respectively, and a good polydispersity index below 0.25 for both formulations. The nanocapsules showed good stability when stored at 40 ºC and room temperature for 30 days. The quantitative method was performed with a mobile phase consisting of ammonium ammonium acetate (0.05 M adjusted to pH 5.0 with acetic acid) and acetonitrile 60:40 (v/v); the flow rate was 0.8 mL/min, UV detection at 230 nm. The analytical method was linear in the range of 5.0-15.0 µg/mL, specific for both oils, accurate, precise (intermediate precision RSD = 1.68% and repeatability RSD = 0.81%) and robust under the evaluated conditions. Therefore, this method can be performed for quantification of mupirocin in polymeric nanocapsules containing both oils.